ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MOTIVASI PETANI DALAM BERUSAHATANI TEBU (STUDI KASUS: PETANI TEBU RAKYAT DI DESA TONJONG WILAYAH KERJA PABRIK GULA TERSANA BARU, KABUPATEN CIREBON) - Lukman Mohammad Baga; Rudie Setiadi (Departemen Agribisnis, FEM-IPB, 2008)
Sugar production growth in Java is quite interesting. Before the economic crisis in 1998, the growth of sugar production was negative, however, after the crisis it became positive. In fact, farmers’ enthusiasm to plant sugar cane started to increase since 2000. This is reflected by the steady larger land area of sugar cane plantation after 2000. Government’s policy on sugar production became more conducive for farmers. There is no more government’s direct intervention on determining sugar cane planting area which is parallel with the strengthening of farmer’s organization (APTRI). APTRI plays important roles in pursuing higher welfare of sugar cane farmers, through achieving higher price of their production. However, it is still clearly unknown, how high is the motivation of farmers to plant sugar cane, and what are the internal and external factors of sugar cane farmers that influence their motivation? This study aims to answer these questions in order to assure the sustainability of sugar cane production in Indonesia. This study employed the case study methods to sugar cane farmers in Cirebon, West Java. The result shows that farmers’ motivation in planting sugarcane is good due to the current sugar business environment that is conducive for them. The role of sugar cane farmers’ association (APTRI) is essential to increase their motivation.